Nuevas citas de Catamblyrhynchus diadema en el noroeste argentino - Di Giacomo, Alejandro G.; Di Giacomo, Adrián S.; Mazar Barnett, Juan; López Lanús, Bernabé M. (El Hornero, 1997)
Este artículo no cuenta con un resumen.